Influence of symptoms of attention deficit hyperactivity disorder on emotional behavioral problems： parallel mediating effect of different dimensions of executive function - XUE Yiyun, OU Zixin, HONG Danping, DANG Caiping, ZHU Zhihang, CHENG Daomeng, HU Yingzi, LI Guoquan, YANG Chanjuan, YIN Weizhen (Xin yixue)
Objective To explore the mediating role of behavioral regulation index （BRI） and metacognition index （MI）， two dimensions of executive function， in the relationship between attention deficit hyperactivity disorder （ADHD） symptoms and children’s emotional behavioral problems. Methods A total of 102 children with ADHD aged 6-12 years old who met the Diagnostic and Statistical Manual of Mental Disorders 5th edition （DSM-5） criteria were selected as the study subjects. They were investigated with the self-made general situation questionnaire， the Chinese version of the Swanson Nolan and Pelham， version Ⅳ for ADHD （SNAP-Ⅳ）-parent form， Behavior Rating Inventory of Executive Function （BRIEF） -parent form， and parent edition of Strengths and Difficulties Questionnaire （SDQ）. Parallel mediating effect was analyzed. Results Positive correlations were found among attention deficit， hyperactivity-impulsivity， BRI， MI， and emotional behavioral problems， respectively （r = 0.409-0.934， all P < 0.001）. Attention deficit positively predicted BRI， MI and emotional behavioral problems （β = 1.459， 1.114， 0.294， all P < 0.01）. BRI and MI positively predicted emotional behavioral problems （β = 0.224， β = 0.080， both P < 0.05）， suggesting that behavioral regulation index and metacognition index played a partial mediating role between attention deficit and emotional behavioral problems， and the mediating effect accounted for 58.73% of the total effect. Hyperactive-impulsivity positively predicted BRI， MI and emotional behavioral problems （β = 1.071， 2.057， 0.223， all P < 0.05）， BRI positively predicted emotional behavioral problems （β = 0.333， P < 0.001）， but MI did not predict emotional behavioral problems （β = 0.026， P > 0.05）， indicating that only behavioral management played a partial mediating role between hyperactive-impulsivity and emotional behavioral problems. The mediating effect accounted for 64.72% of the total effect. Conclusion BRI and MI play a mediating role between emotional behavioral problems and symptoms in ADHD children.